“What Makes Us Strong?”: Dyadic Coping in Italian Prospective Adoptive Couples - Canzi, Elena; Donato, Silvia; Ferrari, Laura; Parise, Miriam; Pagani, Ariela Francesca; Lopez, Giulia; Rosnati, Rosa; Ranieri, Sonia (Frontiers in Psychology, 2019)
Becoming an adoptive parent is a particularly stressful transition, given the additional challenges couples have to face. Dyadic coping, an under-investigated dimension in the adoption literature, may play a relevant role for prospective adoptive couples’ ability to better cope with the adoptive process. The general aim of the present study was to investigate the association between dyadic coping and relationship functioning, in terms of relationship satisfaction and couple generativity, among prospective adoptive couples. Participants were 103 prospective adoptive couples pursuing international adoption in Italy. Couples were asked to fill in a self-report questionnaire. Results of the Actor-Partner Interdependence Model showed that prospective adoptive partners reported high levels of positive and common dyadic coping and low levels of negative dyadic coping - suggesting partners’ ability to successfully cope together with a common stressor - a high level of relationship satisfaction, and an average level of couple generativity. Moreover, analyses showed significant actor effects of one’s own perception of the partner’s dyadic coping (positive, negative, and common) on one’s own relationship satisfaction and on couple generativity for both wives and husbands. With regard to partner effects, we found that both partners’ perceptions of the other’s dyadic coping responses (positive, negative, and common) were associated with the other’s relationship satisfaction, with the only exception of wives’ perceptions of common dyadic coping, which were not associated with their husbands’ relationship satisfaction. As for couple generativity, the only significant partner effect referred to negative dyadic coping responses for both wives and husbands.